Academic Senate Minutes 2007-03-08 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 2/22/07 approved. President's Report. Vice President of Administration and Finance Report. Report on First Year Experience Pilot. Approval to run election granted. Discussion of Accreditation of the Business Department. Sabbatical Policy revision approved.